SDFAC:software defined flow access control mechanism - Xiu-lei WANG; Guo-min ZHANG; Chao HU; Ming CHEN; Xiang-lin WEI (Tongxin xuebao)
The software defined networking paradigm decouples control plane from data plane,offering flexible centralized control and fine grain flow management.Based on these advantages,a novel software defined access control mechanism SDFAC was proposed.Firstly,an analysis of the access control model was given from the flow granularity,and the precondition for the fine-grained access control was deduced from the model.Secondly,the framework and basic working process of the SDFAC was described.The flow authentication protocol was designed to support the function of SDFAC.Finally,the experiment results prove the feasibility and availability of SDFAC.